Pengaruh Struktur Aktiva dan Ukuran Perusahaan Terhadap Harga Saham Pada Perusahaan Sub Sektor Farmasi di Bursa Efek Indonesia - Erniwati Madya; Yana Fajriah (Universitas Sains dan Teknologi Komputer, 2021)
The capital market is one of the alternative sources of long-term funding among various other alternatives for companies that need funds for the sustainability of the company. The capital market has an important role for the economy of a country because the capital market performs a function, namely as a means for business funding or as a means for companies to obtain funds from the investor community. For this reason, it is necessary to expand research that is supported by a basic theory, so the problem of factors capable of predicting changes in stock prices is proposed, where there are two variables that are thought to have an effect on changes in stock prices in this study. The two variables are asset structure and firm size. In addition, based on various previous research results, it was found that there were gaps or inconsistencies in the research results (gap research) conducted by researchers. On this basis, the title adopted from this research is